Konsep Bela Negara dalam penanggulangan Tindak Pidana Terorisme JW Marriott dan Ritz Carlton - Ishma Safira; Witasya Aurelia Sulaeman; Slamet Tri Wahyudi (Pusat Riset dan Inovasi Nasional, 2024)
The bomb case that occurred at the JW Marriott Hotel and the Ritz Carlton on July 17, 2009 is a form of terrorism attack that shook Indonesia. These attacks not only cause material losses and casualties, but also show the country's vulnerability to threats that could undermine national stability. In this context, the application of the concept of defending the country is very important. Defending the country, which is not only limited to the military aspect but also includes the participation of the community in safeguarding and defending the country, is key in dealing with the threat of terrorism. This study uses a normative research method that examines the relevance of the application of the concept of national defense in dealing with the threat of terrorism, focusing on the JW Marriott and Ritz Carlton bombing cases, as well as their implications for efforts to strengthen Indonesia's national resilience. The results of this study show that the application of the holistic concept of national defense is indispensable to create a strong and resilient defense system against future terrorism threats.